GABAergic neurons in the preoptic area send direct inhibitory projections to orexin neurons - Saito, Yuki; Tsujino, Natsuko; Hasegawa, Emi; Akashi, Kaoru; Abe, Manabu; Mieda, Michihiro; Sakimura, Kenji; Sakurai, Takeshi (Frontiers in Neural Circuits, 2013)
Populations of neurons in the hypothalamic preoptic area (POA) fire rapidly during sleep, exhibiting sleep/waking state-dependent firing patterns that are the reciprocal of those observed in the arousal system. The majority of these preoptic “sleep-active” neurons contain the inhibitory neurotransmitter GABA. On the other hand, a population of neurons in the lateral hypothalamic area (LHA) contains orexins, which play an important role in the maintenance of wakefulness, and exhibit an excitatory influence on arousal-related neurons. It is important to know the anatomical and functional interactions between the POA sleep-active neurons and orexin neurons, both of which play important, but opposite roles in regulation of sleep/wakefulness states. In this study, we confirmed that specific pharmacogenetic stimulation of GABAergic neurons in the POA leads to an increase in the amount of NREM sleep. We next examined direct connectivity between POA GABAergic neurons and orexin neurons using channelrhodopsin 2 (ChR2) as an anterograde tracer as well as an optogenetic tool. We expressed ChR2-eYFP selectively in GABAergic neurons in the POA by AAV-mediated gene transfer, and examined the projection sites of ChR2-eYFP-expressing axons, and the effect of optogenetic stimulation of ChR2-eYFP on the activity of orexin neurons. We found that these neurons send widespread projections to wakefulness-related areas in the hypothalamus and brain stem, including the LHA where these fibers make close appositions to orexin neurons. Optogenetic stimulation of these fibers resulted in inhibition of orexin neurons. These observations suggest direct connectivity between POA GABAergic neurons and orexin neurons.